What Remains of Manhood - Eleonora Belligni (Journal of Interdisciplinary History of Ideas)
Between the late Middle Ages and the Early Modern period, the emergence of the European territorial state was accompanied by a change in the gender balance, as women gained new and increased opportunities for leadership. In the sixteenth century, the new political anthropology, in the light of the socio-political, religious and cultural phenomena that changed the dynamics of the various European regions, elaborated theoretical constructions of government, the state, the distribution of functions, legitimacy and the foundations of consensus. It is a cultural operation to define a masculine power that considers women as the embodiment of an exception or an aberration. The consequence is that this masculinisation of power is typical of the Renaissance and does not belong to the political culture of previous centuries. By extension, the so-called ‘paradigm of exceptionalism’ (in the modern state, women in power are the exception that proves the rule) is an invention, or rather a recreation, of modern political philosophy, which reflects on the relationship between sovereignty and power and assigns it a masculine identity value (whose non-feminine character is emphasised). The hypothesis will be tested in the relationship between different types of textual sources in Early Modern Italy: namely, the reports of ambassadors and nuncios in a period stretching from Isabella of Castile to Elizabeth I Tudor; political treatises; travelogues.